Analysis of Legal Certainty and Proof Strength of Deeds Cyber Notary - Friko Rumadanu; Benny Djaja (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
The phenomenon of authentic deeds in digital form which is a product of cyber notary It is interesting for the author to analyze the aspects of legal certainty that will be obtained by the parties listed in the deed and the extent to which the deed has evidentiary power in the eyes of the law in force in Indonesia. The problem that will be analyzed in this research is legal certainty and the strength of deed evidence notary. This research aims to determine the legal certainty and evidentiary strength of the deeds made by notary. The research method used in this research is normative juridical research with a statutory approach and a conceptual approach. The research results show a contradiction between two regulations governing digital documents such as deeds cyber notary. The UUJN clearly states that an authentic deed must be made in the presence and presence of the parties concerned, whereas the ITE Law pays attention to this element by replacing it with an online presence. The conclusion from this research is the legal certainty of deeds cyber notary bias and evidentiary strength of the deed Cyber notary weak because there is no legal umbrella to regulate explicitly